A Patchwork of Passages: On the Nature of Imitation in Galileo’s Alphabet and Painting Metaphors - Kelly, Peter (Ciceroniana On Line, 2020)
In the Dialogo sopra i due massimi sistemi del mondo, Galileo states that he has a more authoritative book than those of Aristotle, one which is capable of representing a unified theory of nature; he calls it the alphabet. Galileo’s metaphor of the alphabet is adapted from Lucretius’ De rerum natura and indicates Galileo’s turning towards the primary constituents of the material world, ahead of the study of texts; he also compares the scientist to a painter capable of imitating the finest details of the physical world. Both these images emphasize the aesthetic nature of the scientist’s work. This paper argues that Galileo is responding to a series of aesthetic works on poetic imitation, while both metaphors link the activities of the scientist with that of the artist, where discovering and making tangible the underlying order of matter is fundamentally a creative activity, and where the scientist not only reveals, but invents the profound beauty in nature.